Towards Stimulating Tools for Advancement of Environmental Conservation through Promoting of Psychological Instruments - Md. Rahimullah, Miah; Mohamed Sharif, Mustaffa; Samsiah, Jayos; Nor Hasniah, Ibrahim; Sopian, Bujang; Jamayah, Saili; Alexander Kiew, Sayok (Canadian Center of Science and Education, 2019)
The explorative field observation on Environmental Conservation Psychology (ECP) is multi-diversified with collective and conjectural outlook. ECP provides a better understanding of the way in which conservation awareness, attitude, ethics, culture and well-being are affected by physical environments, social settings and built-in environment. The goal is to stimulate more attention be paid to ensure the effectiveness of environmental conservation and highlight psychological instruments required to develop new interdisciplinary approaches with innovative ways in prevailing challenges for the present and upcoming generations. Primary data were collected from a sample of respondents at the Lawachara National Park (LNP) in Moulvibazar district of Bangladesh and secondary data were obtained from diverse sources. The research denoted and investigated by various disciplines and fields including environmental behaviors studies, positive psychology, person-environment studies, human-nature science and ecological psychology. The study showed about 70% of indigenous respondents opined on positive attitudes for environmental conservation to compare with 55% in others. The study identified approximately 65% of respondents stated for development of environmental education among local communities for promoting positive psychology surrounding the national park. This study focuses the importance of understanding this multidimensional psychological research as it is to inform about the environmental conservation perspectives that have contributed to and shaped the learning with high internal conservation stability, dependability, uniformity, and attractiveness with social bonding at LNP. This study represents the environmental design, manage, protect and restore conserving of biodiversity towards national parks that influence human behavior, predict and the likely outcomes when these conditions are not met and diagnose problem situations. This study links at solving complex environmental conservation problems in the pursuit of individual well-being within a longer community through human-environment conservation interactions.